Apprearance of Mutan Corn (Zea mays L.) Strains and Genetic Correlation Between Characters - Makhziah; Sukartiningrum; Ahmad Surya Adi Tama (Nusantara Science and Technology Proceedings)
This study aims to determine the appearance and correlation of the genotype and phenotype of inbred maize mutant lines (M1). Ten inbred maize mutant lines (M1) were grown in a randomized block design (RBD) which was repeated 3 times. The results obtained phenotypic differences of ten mutant lines of inbred maize (M1) for the characters of plant height, number of leaves, time of appearance of male flowers, female flowers, and seed weight. Genetic correlation perfectly correlated (+1) on the anthesis character with the cooking time of cobs and silking with the cooking time of cobs. Plant height was significantly correlated with leaf number and stover weight; whereas seed weight had a significant genotype correlation with leaf number, antesis and stover weight.